Toxicity of the mycotoxin ochratoxin A in the light of recent data. (May 2013) - Malir, Frantisek; Ostry, Vladimir; Novotna, Eva
Abstract Ochratoxin A (OTA) is a ubiquitous, naturally occurring chlorophenolic mycotoxin produced in contaminated food and feed by fungi of genera Penicillium and Aspergillus. OTA is a common contaminant of various foodstuffs of both plant and animal origin. OTA represents significant risk to human and animal health. OTA has been shown to be nephrotoxic, hepatotoxic, teratogenic, immunotoxic, neurotoxic, genotoxic and carcinogenic (possible human carcinogen-group 2B), being characterized by species and sex differences in sensitivity. In some aspects OTA remains as a controversial topic. Its metabolism, genotoxicity and mechanism of action for renal carcinogenicity have been discussed.